Analisis Kesulitan Belajar Matematika Kelas 2 SD Muhammadiyah 3 Assalaam - Pramiswari, Elok Dara; Suwandayani, Beti Istanti; Deviana, Tyas (Jurnal PGSD, 2023)
In order to prepare students to be able to apply mathematics and mathematical thinking patterns in everyday life and in studying various sciences at school, difficulties in understanding material in mathematics subjects experienced by students, especially in elementary schools, need to be addressed immediately.  This research aims to analyze the difficulties experienced by grade 2 students at SD Muhammadiyah 3 Assalaam.  This research is a type of descriptive research with a qualitative approach, the data collection techniques used are observation, interviews and documentation.  Data validation techniques use technical triangulation, source triangulation and time triangulation.  The research was carried out in class 2 of SD Muhammadiyah 3 Assalaam, Blimbing District, Malang City, East Java.  The results of the research show that mathematics is a subject that is considered difficult by the majority of grade 2 students at Muhammadiyah Assalaam Elementary School, especially in the multiplication operation material. This is caused by various factors originating from internal and external factors.